An experimental investigation on bending stiffness and neutral axis depth variation of over-reinforced high strength concrete beams - Mohammadhassani, M.; Jumaat, Mohd Zamin; Chemrouk, M.; Maghsoudi, A.A.; Jameel, M.; Akib, S. (Nuclear Engineering and Design, 2011)
The present work is an attempt to study the neutral axis variation and the evolution of the moment inertia with the loading of over reinforced high strength concrete sections in conjunction with ACI 318-05. In this sense, four high strength concrete beams, having different tension reinforcement quantities expressed as proportions of the balanced steel ratio (0.75Ï b, 0.85Ï b, Ï b, 1.2Ï b) were tested. Measurements of the deflection and the reinforcement and concrete strains of all specimens were made during the loading process. The load-neutral axis depth variation and the load-section stiffness curves were drawn. The slope of the line connecting the origin of the first crack to the initial yielding of the failure point in the neutral axis depth-load graphs shows the rate of ductility; ductile behaviour in the beam increases as the slope becomes steeper. Based on the results of this study, it is recommended that the modulus of elasticity of concrete E c be reviewed and evaluated at a stress higher than 0.5 fâ² c for the determination of the cracked moment of inertia.